Implementasi Tradisi “Angkaan Bherkat” dalam Peringatan Maulid Nabi: Sebuah Kajian Etnografi di Pulau Bawean - Hodaifah; Widodo, Wahono; Gunansyah, Ganes (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
The commemoration of the Prophet Muhammad's birthday on Bawean Island is always interesting to discuss, this is because there are unique and interesting things that are not owned by other regions. One of the uniqueness of the commemoration is the model of angka'an bherkat which is packaged in such a way that makes people amazed when they see it. The purpose of this study is to explore the period of the type of angka'an bherkat, examine its positive and negative impacts in the implementation of the maulid commemoration and explain the role of the maulid commemoration in providing financial contributions to a region. This study is a qualitative study using an ethnographic approach through observation, documentation and in-depth interview methods. The targets of this study are the general public, community leaders and youth. The results of this study indicate that there are 5 periods of angka'an bherkat in the commemoration of the Prophet's birthday on Bawean Island, namely: (1) the usungan period; (2) the tengghuk period (3) the bekol and ceppo period (4) the plastic bucket period, and (5) the period of all containers. In every activity there are always positive and negative impacts as well as the commemoration of the Prophet's birthday with the angka'an bherkat model. However, the commemoration of the Prophet's birthday on Bawean Island provides a large financial contribution to the development of a region.